The Study of regular physical activity status and perception of barriers for performing it in adolescents - Valiollah Padehban; Reza Negarandeh*; Nasrin Nikpeyma (Tehran University of Medical Sciences, 2018)
Background & Aim: Regular physical activity is a major aspect of healthy lifestyle and control and prevention of many chronic diseases. Also, perceived barriers to physical activity among various populations are different. This study aimed to determine the status of regular physical activity and perceived barriers to performing it in adolescents who studying in the junior high school. Materials and Methods: This cross-sectional study has used a stratified random sampling with proportional allocation on 280 subjects among the students at the city of Babol. For data collection, three questionnaires for demographic status, physical activity and perceived barriers to physical activity have been used. The data analyzed by using descriptive statistics and chi-square tests. Results: The results showed that most of students (61.1 %) didn't have regular physical activity, and only 38.9 % had regular physical activity. The most common perceived barriers to physical activity of students has been listed as: lack of relatives' supports (53.6 %), to being far from sports places (35 %), and lack of enough self-confidence (33.2 %). Conclusions: This study showed the majority of students during the high school years, are not engaging in regular physical activity. As well, there are many barriers to having regular physical activity. Therefore it is necessary to implement health policies about the improving physical activity at a school and community levels, increased access to places for physical activity, and eliminate perceived physical activity barriers.   l